1999
DOI: 10.1101/gad.13.7.792
|View full text |Cite
|
Sign up to set email alerts
|

Toll receptor-mediated Drosophila immune response requires Dif, an NF-kappa B factor

Abstract: The induction of immunity genes in Drosophila has been proposed to be dependent on Dorsal, Dif, and Relish, the NF-B-related factors. Here we provide genetic evidence that Dif is required for the induction of only a subset of antimicrobial peptide genes. The results show that the presence of Dif without Dorsal is sufficient to mediate the induction of drosomycin and defensin. We also demonstrate that Dif is a downstream component of the Toll signaling pathway in activating the drosomycin expression. These resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
205
2
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(211 citation statements)
references
References 41 publications
1
205
2
3
Order By: Relevance
“…Similarly, several lines of evidence indicated that the NF-κB-like factor Dorsal, which is activated by the Toll pathway during development, is not required for the expression of antimicrobial peptides. Initially, Tony Ip and colleagues 32 (in Worcester, United States) generated a fly line carrying a small deletion that spans both Dif and Dorsal. By re-introducing P E R S P E C T I V E S (FIG.…”
Section: Toll Regulates the Antifungal Responsementioning
confidence: 99%
“…Similarly, several lines of evidence indicated that the NF-κB-like factor Dorsal, which is activated by the Toll pathway during development, is not required for the expression of antimicrobial peptides. Initially, Tony Ip and colleagues 32 (in Worcester, United States) generated a fly line carrying a small deletion that spans both Dif and Dorsal. By re-introducing P E R S P E C T I V E S (FIG.…”
Section: Toll Regulates the Antifungal Responsementioning
confidence: 99%
“…8 This susceptibility phenotype was shown to be due to a specific failure to synthesize the antifungal peptide Drosomycin in the Drosophila fat body (the equivalent of the mammalian liver) as a consequence of defective activation of dorsal immunity factor (DIF), another transactivator with homology to NFkB. 9 Further investigations have shown that both fungal and Gram-positive infection activate the Toll pathway through the cleaved, activated form of Spatzle, and recruit members of an intracellular signaling cascade including the deathdomain-containing adaptor proteins dMyD88 and Tube, as well as the serine-threonine kinase Pelle, leading to degradation of the inhibitor protein Cactus and nuclear translocation of DIF. Notably, host defense against Gramnegative bacterial infection in Drosophila is mediated by a distinct recognition and signaling pathway defined by the Imd gene.…”
Section: Drosophila Toll and The Identification Of Mammalian Tlrsmentioning
confidence: 99%
“…It maps directly adjacent to Dif and, under certain conditions, can replace Dif function in the immune response. 57,58 We thus analyzed the phenotypes associated with a deletion for both dorsal and Dif, Df(2L)J4. 57 As a control for this study we examined the dl P01313 mutant, which specifically inactivates dorsal function.…”
Section: Neither Dif Nor Relish Is Required For Hid Induction In Salimentioning
confidence: 99%